Samsung : Lee Byung Chull, créateur d’un modèle mondial (1938-1987) - Rang-Ri Park-Barjot (Les Cahiers de Framespa)
Samsung (or the “three star” firm) was founded in 1938 by Lee Byung Chull, an exceptional entrepreneur. Initially, the Group produced low-quality, cheap products, then step-by-step became a technological leader thanks to an efficient industrial model. In spite of its diversification, Samsung became a world leader of the digital era. Samsung realized spectacular breakthroughs in the electro-technical and electronics sectors thanks to its subsidiary Samsung Electronics, a world leader in television and electronic components. It is the twentieth brand in the world and is now one of the most powerful groups in Asia. As with other chaebols (conglomerates), Samsung is the result of the actions of two entrepreneurial generations. However, this family firm was more successful than others thanks to continuous adaptation to changes in world demands, an optimal merger of neo-Confucianism Asian capitalism and American-style big managerial and multidivisional firms, and a massive investment in human capital (in order to close the technological gap with the USA, resulting in it becoming a leader in innovations during the digital era).